The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m110.117093
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Receptor-mediated Rapid Depletion of Nuclear Phosphorylated Akt Depends on Pleckstrin Homology Domain Leucine-rich Repeat Phosphatase, Calcineurin, Protein Phosphatase 2A, and PTEN Phosphatases

Abstract: Akt is an important oncoprotein, and data suggest a critical role for nuclear Akt in cancer development. We have previously described a rapid (3-5 min) and P2X7-dependent depletion of nuclear phosphorylated Akt (pAkt) and effects on downstream targets, and here we studied mechanisms behind the pAkt depletion. We show that cholesterol-lowering drugs, statins, or extracellular ATP, induced a complex and coordinated response in insulin-stimulated A549 cells leading to depletion of nuclear pAkt. It involved protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 44 publications
5
55
0
1
Order By: Relevance
“…Different types of statins have been reported to decrease the levels of phosphorylated Akt in several cell lines, and our group has shown that pravastatin, simvastatin and atorvastatin lower the insulininduced nuclear pAkt accumulation without affecting the total Akt levels in A549 cells (15). This effect is mediated by P2X7, and is associated with altered phosphorylations of downstream targets of pAkt, including GSK3β and cyclin D1 (13,14). Here we investigated the cellular effects of the long-term treatment with atorvastatin to gain insight into their mode of action in the prevention of cancer.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Different types of statins have been reported to decrease the levels of phosphorylated Akt in several cell lines, and our group has shown that pravastatin, simvastatin and atorvastatin lower the insulininduced nuclear pAkt accumulation without affecting the total Akt levels in A549 cells (15). This effect is mediated by P2X7, and is associated with altered phosphorylations of downstream targets of pAkt, including GSK3β and cyclin D1 (13,14). Here we investigated the cellular effects of the long-term treatment with atorvastatin to gain insight into their mode of action in the prevention of cancer.…”
Section: Resultsmentioning
confidence: 86%
“…Mutaton/deletion of PTEN has been reported in many cancers (20): therefore, the pAkt/PTEN axis is currently attracting great interest for its role in carcinogenesis. Moreover, we provided evidence for the involvement of PTEN, together with the protein phosphatases PHLPP1, PHLPP2, PP2A and calcineurin, in the rapid statin-induced P2X7-mediated nuclear pAkt depletion (14).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Alguns estudos têm relacionado a atividade de PTEN e PP2A (Mistafa et al, 2010;Nho e Kahm, 2010;Bononi et al, 2011;Xu et al, 2011) …”
Section: N T R O D U ç ã O | 10unclassified